Induced immunosuppression in critical care: diagnostic opportunities in clinical practice - E. V. Grigoryev; V. G. Matveeva; D. L. Shukevich; A. S. Radivilko; E. A. Velikanova; M. Yu. Khanova (Бюллетень сибирской медицины, 2019)
The immune system in critical illnesses initiates local inflammation in the damaged area. In the absence of a balance between local and systemic inflammations, an infectious or non-infectious systemic inflammatory response follows, which has a stage of "hyper inflammation - compensatory anti-inflammatory response", that may result in multi-organ failure. The final stage of critical ill-nesses, therefore, will be characterized by induced immunosuppression with the impaired function of neutrophils, monocytes, macrophages and dendritic cells and release of myeloid-derived suppres-sor cells. The aim of the review is to evaluate the contribution of various components of the im-mune response to the formation of induced immune suppression from the perspective of candidate diagnostic markers.